Diabetic macular edema, innovative technologies and economic impact: New opportunities for the Lombardy Region healthcare system?. Issue 4 (14th December 2017) - Foglia, Emanuela; Ferrario, Lucrezia; Bandello, Francesco; Ferri, Camilla; Figini, Innocente; Franzin, Michela; Gambaro, Gianpiera; Introini, Ugo; Medaglia, Massimo; Staurenghi, Giovanni; Tadini, Patrizia; Fomiatti, Andrea; et al.
Abstract: Purpose: Diabetic macular edema (DME) is a leading cause of vision loss and blindness. The aim of this study was to evaluate the economic benefits of introducing additional alternative technologies (Dexamethasone intravitreal implant – DEX – and Aflibercept injections), compared with the historical scenario of Ranibizumab intravitreal injections. Methods: A 3‐year budget impact model was developed, taking into consideration the perspective of the Lombardy Region Healthcare Service (LRHS). Total administration costs (real‐life data retrieved from clinical practice at three Departments of Ophthalmology) as well as costs related to the management of potential adverse events (information collected from the literature) were analysed. Results: Over a 36‐month horizon, the results showed that a higher consumption of DEX could lead to significant economic savings for the Regional Healthcare Service, ranging from a minimum of −4.35% (if DEX were used only in the second‐line of treatment) to a maximum of −12.97% (if DEX were used in both the first‐line and second‐line), including the potential impact of adverse events. Therapy costs with Aflibercept and Ranibizumab were similar. Conclusions: This study demonstrates that concentrating all eligible patients within the Ranibizumab regimen is unlikely to represent a cost‐effective strategy. Indeed, significant economic advantages would be achieved by introducing the other licensed alternatives, Dexamethasone implant and Aflibercept, thus optimising DME Italian healthcare expenditure. The results demonstrate DEX as an advantageous technological alternative for the target population affected by DME, both as a first‐ and second‐line treatment option, reducing the economic burden of the pathology for the Regional/National Health Service.